THE IMPORTANCE OF CONSTRUCTIVE FEEDBACK FOR DEVELOPING SKILLS IN COMPANIES - Mulangue, José (Seven Editora, 2026)
Providing feedback is essential for promoting employee performance in modern organizations, especially when it comes to performance. Most studies have shown that feedback increases motivation, employee engagement, and productivity. The question arises, how to provide feedback constructively? Effective feedback can and should be honest, specific, and timely, as it is essential to be clear about the purpose of the feedback and the specific behavior or outcome of what is being addressed. The objective of this article is to analyze the importance of constructive feedback for skill development in companies. The article presents several studies that have presented results on the influence of constructive feedback for improving employee skills, which confirm the positive effects of feedback identified in the organizational context and the main strategies for this process to be successful and achieve the proposed objectives.